“Seafood not Slavefood”: Advokasi Aktivisme Transnasional untuk Mengakhiri Praktik Perbudakan Modern di Industri Perikanan Thailand - Roihanatul Maziyah; Rr. Hermini Susiatiningsih (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
In 2013, EJF (Environmental Justice Foundation) launched a global campaign named